Fatal Attraction : A New Measure of Contagion - Bayoumi, Tamim (IMF Working Papers; Working Paper ;, 2003)
This paper proposes a new measure of contagion that is good at anticipating future vulnerabilities. Building on previous work, it uses correlations of equity markets across countries to measure contagion, but in a departure from previous practice it measures contagion using the relationship of these correlations with distance. Also in contrast to previous work, our test is good at identifying periods of "positive contagion," in which capital flows to emerging markets in a herd-like manner, largely unrelated to fundamentals. Identifying such periods of "fatal attraction" is important as they provide the essential ingredients for subsequent crises and rapid outflows of capital.